2018
DOI: 10.1371/journal.pone.0198450
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of stuttering determined by latent class analysis in two Swiss epidemiological surveys

Abstract: AimsAssociations between stuttering in childhood and a broad spectrum of risk factors, associated factors and comorbidities were examined in two large epidemiological studies. Subtypes of stuttering were then identified based on latent class analysis (LCA).MethodsData were from two representative Swiss population samples: PsyCoLaus (N = 4,874, age 35–82 years) and the ZInEP Epidemiology Survey (N = 1,500, age 20–41 years). Associations between stuttering and sociodemographic characteristics, familial aggregati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 119 publications
4
13
0
Order By: Relevance
“…The high rates of asthma in CWS in the present study is in agreement with past reports [ 143 , 149 , 151 , 171 ]. In fact, another atopic disease, hay fever, was reported to correlate with an earlier onset of stuttering and chronicity [ 172 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The high rates of asthma in CWS in the present study is in agreement with past reports [ 143 , 149 , 151 , 171 ]. In fact, another atopic disease, hay fever, was reported to correlate with an earlier onset of stuttering and chronicity [ 172 ].…”
Section: Discussionsupporting
confidence: 94%
“…In clinical cohorts, concomitant language, speech, and behavioral disorders (e.g., expressive language, receptive language, articulation, phonology, and ADHD) are commonly reported with stuttering [ 141 , 142 ]. Prior studies also suggest higher rates of socioemotional, psychological distress and anxiety in CWS compared to CWNS [ 126 , 143 148 ]. In a study of 2,628 CWS, a majority (62.8%) had comorbid disorders [ 149 ].…”
Section: Introductionmentioning
confidence: 98%
“…As the diagnosis of stuttering could also be related to acquired stuttering, we analyzed in detail the occurrence of comorbidities in the cohorts with speech disorders and the total insured population. For the insurance year 2017, we evaluated the co-occurrence of disorders and comorbidities for which a coexistence with stuttering has previously been reported in the literature, including: anxiety disorders (ICD10 codes F40.x, F41.x, and F93.0) (Iverach et al, 2009); ADHD (F90.x) (Ajdacic-Gross et al, 2018); tic disorders and Tourette syndrome (F95.x) (Ajdacic-Gross et al, 2018); personality disorders (F60.x, F61.x, and F62.x) (Iverach et al, 2009); specific developmental disorders of scholastic skills (F81.x) (Ajdacic-Gross et al, 2018); atopic disorders (J30.1-J30.4, J45.0, L20.x, and J30.1-J30.4) (Ajdacic-Gross et al, 2020); mental retardation (F70-F74); chromosomal anomalies (Q90x-Q99.x); and neurodevelopmental disorders (G40.x, G80.x. G91.x, G93.0, and G93.1) (Neumann et al, 2017).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…These numbers were compared against the prevalences observed among the general insurance population aged 0-19 years for the insurance year 2017. Table 3 shows elevated odds ratios in patients with developmental disorders of speech and language (F80) compared with those for the general population for: atopic dermatitis (L20) (Ajdacic-Gross et al, 2020); phobic disorders (F40, F41, and F93) (Iverach et al, 2009); ADHD (F90) (Ajdacic-Gross et al, 2018); tic disorders and Tourette's syndrome (F95) (Ajdacic-Gross et al, 2018); personality disorders (F60) (Iverach et al, 2009); specific developmental disorders of scholastic skills (F81) (Ajdacic-Gross et al, 2018); intellectual disabilities (F70-F74); chromosomal anomalies (Q90 and Q93); and neurodevelopmental disorders (G40, G80, G91, G93, and G93) (Neumann et al, 2017). Table 4 shows a similar distribution of concomitant disorders and comorbidities among patients with FIGURE 3 | Annual total number (A,C) and the crude annual incidence [in%, (B,D)] of male and female patients in each 1-year age group diagnosed with a disorder of speech and language (A,B), as coded by at least one confirmed ICD-10 diagnosis of developmental disorders of speech and language, stuttering, or cluttering, and those diagnosed with stuttering (C,D) in insurance year 2017; y = years.…”
Section: Concomitant Disorders and Comorbiditiesmentioning
confidence: 99%
“…. Recently, Ajdacic-Gross et al (2018) identified atopic diseases as factors associated with stuttering which applies more generally to childhood speech disorders Silverberg 2016a, 2016b), ADHD (Buske-Kirschbaum et al 2013;Schans et al 2017;Tsai et al 2013) and other neurodevelopmental disorders. Additional evidence is accruing which shows that psychosocial stressors impact the immune system at an early age (Danese and Lewis 2017) and psychosocial stressors and the immune system impact brain development jointly at critical periods .…”
Section: ))mentioning
confidence: 99%